Evaluation of the effects of curcumin, erdosteine, vitamin E and vitamin C on paracetamol toxicity - Nursah Basol; Cansel Ozmen; Seda Ocakli; Selcuk Cetin (Medicine Science, 2022)
Paracetamol toxicity is one of the most common causes of drug induced toxicity in the world. This study aims to investigate the efficacy of curcumin, erdosteine, vitamin E and vitamin C administration in paracetamol-induced liver damage in comparison with N-acetyl cysteine (NAC) in the treatment and prevention of liver toxicity due to paracetamol poisoning. 49 Wistar-Albino rats were used for this study. The rats were randomly divided into 7 groups. Group 1, which was the control group, received no drug administration. All the other groups received the minimum toxic dosage of paracetamol (1 gr/kg). Group 2 was not administered any other drug. Curcumin (100 mg/kg) was administered to Group 3. Group 4 received Vitamin E (170 mg/kg) and Group 5 received Vitamin C (300 mg/kg). Erdosteine (150 mg/kg) was administered to Group 6 and the last group (group 7) was received NAC for 2 days. After 72 hours, the experiment was completed. Liver and kidney tissues and blood samples were collected. AST and ALT values were higher in PCT group compared with the control group. Additionally, in PCT group, SOD and GSH-PX levels were lower while MDA levels were found to be higher in comparison to the control group. In the treatment groups, curcumin proved to be the most efficient agent, with NAC and erdosteine following. Histopathological images supported that curcumin played a key role in preventing liver damage. On the other hand, the results indicated no significant contribution of vitamin E and C in reducing paracetamol induced liver damage. In the light of the results, it is indicated that oxidative stress and lipid peroxidation are principal mechanisms of paracetamol induced liver damage, whereas curcumin and erdosteine are efficient agents in preventing said damage. Furthermore, the findings of the study suggest that curcumin in particular can be used as an alternative drug to NAC after further research on humans. [Med-Science 2022; 11(2.000): 465-70]